(untitled) (Al-Qamar, 2023)
Bishr Ibn Abī Khāzim Al-Asadī is an Arab pre-Islamic poet who is considered one of the good and famous eloquent Arabic poets of the first pre-Islamic era. He is different from Bishr ibn Marwān Al-Umawī (also known as Bishr ibn Abī Khāzim, the Arab poet) and each has a distinctive poetic style characterized by exquisite and eloquence. Bishr ibn Abī Khāzim Al-Asadī was born in Yemen and is believed to have been from one of the great tribes who controlled some areas of Arabia at that time. He was a famous poet of his time, known for his poetry dealing with topics as diverse as love, beauty, nature, society, war, and heroism. One of the famous poems attributed to him is the poem "Namlah Ibn ʿAjlān", in which he describes the beauty and virtues of a woman named an ant. His poetry is characterized by a refined and humorous style that attracts and interests the reader. Bishr Ibn Abī Khāzim moved between cities and tribes, and he used to meet poets and compete with them in poetry and was distinguished by his ability to present the idea in a smooth and attractive style, and then his poems were considered one of the important Arab literary works in the pre-Islamic era. So, we will discuss in this study the life of Bishr Ibn Abi Khazim and his poetic eloquence. This study will illuminate the poetic status of Bishr to the readers.